Preparation method of p-type doped three-dimensional graphene wrapped ZIF composite wave absorbing material

By doping excessive Co2+ ions in three-dimensional graphene with ZIF-67 and doping at high temperature, a p-type doped three-dimensional graphene encapsulated ZIF composite absorbing material is solved, and the problem of poor bonding of three-dimensional graphene and porous frame materials is achieved, and higher absorbance performance and structural stability are achieved.

CN116144322BActive Publication Date: 2025-05-02ZHEJIANG SCI-TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211659975.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-05-02
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

The poor bonding of existing three-dimensional graphene with porous frame materials leads to poor structural stability, which limits the further improvement of wave absorption performance.

Method used

By doping excess Co2+ ions in the three-dimensional graphene, it is effectively combined with the three-dimensional porous frame of ZIF-67, and p-type doping is performed through the high-temperature doping principle to form a p-type doped three-dimensional graphene-encapsulated ZIF composite absorbing material.

Benefits of technology

The carrier concentration and conductivity of three-dimensional graphene are improved, the wave absorption performance is enhanced, and the material structure is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004010203350000081
    Figure BDA0004010203350000081
Patent Text Reader

Abstract

The present invention relates to the field of wave absorbing materials. The present invention discloses a method for preparing a p-type doped three-dimensional graphene-wrapped ZIF composite wave absorbing material, comprising: step 1: preparing a graphene oxide dispersion; step 2: mixing ZIF-67 (Co) with the graphene oxide dispersion, adding an excess of Co-containing 2+ Cobalt compound, and then adjust the pH to below 3.5 to obtain three-dimensional graphene-wrapped ZIF powder; step 3: pass borane into high-temperature reduction sintering to obtain p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material. The p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material prepared by the method of the present invention has ZIF stably fixed between three-dimensional graphene sheets, which can effectively prevent graphene from stacking itself, has good structural stability, and can maintain its excellent conductivity. The present invention utilizes high-temperature doping to perform p-type doping on three-dimensional graphene, thereby increasing the carrier concentration, achieving better impedance matching, and making its absorbing performance more excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wave-absorbing materials, and in particular to a method for preparing a p-type doped three-dimensional graphene-wrapped ZIF composite wave-absorbing material. Background Art

[0002] Three-dimensional graphene is a new type of carbon nanomaterial composed of two-dimensional graphene on a macroscopic scale. It can overcome the π-π force between graphene sheets while maintaining the excellent characteristics of graphene's ultra-large specific surface area and ultra-high conductivity, effectively blocking the self-disordered stacking of graphene sheets and thus achieving the stability of its macroscopic structure. Its unique zero-bandgap structure, ultra-fast carrier mobility, low density, large specific surface area, and high mechanical strength have the advantages of maintaining its excellent conductivity and excellent mechanical properties in the application of composite materials due to its three-dimensional structural characteristics. Therefore, from visible light to infrared wave bands, three-dimensional graphene exhibits good wave absorption characteristics. The electrical conductivity of three-dimensional graphene is large, but the microwave magnetic permeability is relatively small, which limits the further improvement of the wave absorption performance of three-dimensional graphene. Therefore, scholars have tried to functionalize graphene, add ferromagnetic nanoparticles to it or disperse it in a polymer matrix, so as to prepare carbon tube wave absorbing materials with light weight, strong absorption and wide absorption frequency band.

[0003] Metal-organic framework materials (MOFs) are a type of coordination polymer that has developed rapidly in the past two decades. They have a three-dimensional pore structure, generally with metal ions as the connection points, and organic ligands supporting the 3D extension of space. They are another important new type of porous material besides zeolites and carbon nanotubes. The three-dimensional porous structure of the sintered carbon framework is naturally suitable for absorbing materials to have good impedance matching. If it is compounded with good electrical and magnetic conductors, it will be an excellent microwave absorbing material. ZIF-67 (Co) itself uses magnetic particles of metal Co as the connection point, and is a potential substrate for absorbing materials. However, there are still many problems in how to perfectly combine three-dimensional graphene with a porous framework and then load magnetic particles to prepare absorbing materials with good absorbing performance, such as the poor binding of three-dimensional graphene with porous framework materials, and the easy self-stacking of graphene sheets in three-dimensional graphene, resulting in poor structural stability. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material. The p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material prepared by the method of the present invention has ZIF stably fixed between three-dimensional graphene sheets, so that graphene can effectively prevent self-stacking in the composite material, maintain its unique structure, good stability, and can maintain its excellent conductivity. The present invention uses the principle of high-temperature doping to perform p-type doping on three-dimensional graphene, improve the carrier concentration, better impedance matching, and make its absorbing performance more excellent.

[0005] The specific technical solution of the present invention is: a method for preparing a p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material, comprising the following steps:

[0006] Step 1: preparing graphene oxide dispersion.

[0007] Step 2: Mix ZIF-67(Co) and graphene oxide dispersion in a ratio of 80-110 g: 200 mL, stir evenly and add excess Co-containing 2+ The cobalt compound is ultrasonically treated, and then acid is added to adjust the pH to below 3.5, heated at 75-85° C. in air with stirring until the water is basically evaporated, and then dried to obtain three-dimensional graphene-wrapped ZIF powder.

[0008] Step 3: Put the three-dimensional graphene-wrapped ZIF powder obtained in step 2 into a tube furnace, introduce borane, heat to 700-1100° C. and sinter for 2-8 hours to obtain a p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material.

[0009] The preparation principle of the present invention is as follows: Step 1 first prepares graphene oxide with oxygen-containing groups, and in Step 2, uses the N on the three-dimensional porous framework of ZIF-67 (Co) to add excess Co 2+ ions are coordinated with N and attached to the three-dimensional porous framework of ZIF-67. 2+ On the one hand, the ions are adsorbed on the surface of the ZIF framework through coordination, and on the other hand, the positively charged ions can be combined with the negatively charged graphene oxide through electrostatic adsorption, thereby ensuring the effective combination of ZIF-67 and graphene oxide. On this basis, graphene oxide, with the three-dimensional structure of ZIF-67 and excess Co 2+Ions are used as crosslinking agents to form a three-dimensional graphene precursor, and then acid is added to make the solution in an acidic environment. Due to the instability of ZIF-67 in an acidic environment, the ZIF-67 nanoparticles deposited on the surface of the three-dimensional graphene oxide are dissolved, and the ZIF-67 nanoparticles wrapped in the graphene layer are converted into larger ZIF-67 nanoparticles due to Oswald ripening due to space restrictions, which makes the ZIF-67 nanoparticles wrapped in the graphene oxide sheet. After heating and stirring to volatilize excess nitric acid and drying, it is placed in a tubular furnace and sintered in borane. Through the high-temperature doping principle and the reduction of borane and the high-temperature reduction principle, the graphene oxide is reduced and its p-type doping is achieved, and finally a p-type doped three-dimensional graphene-wrapped ZIF composite wave absorbing material is obtained. The doped graphene increases its carrier concentration, further improves the conductivity, and has more outstanding wave absorbing performance.

[0010] In addition, the pH in step 2 needs to be strictly controlled. If the pH is too high, ZIF cannot effectively collapse to form a three-dimensional graphene-wrapped structure, which affects the microwave absorption performance.

[0011] Preferably, step 1 is specifically as follows:

[0012] Step 1.1: Mix flake graphite powder, concentrated sulfuric acid and phosphoric acid in a container, add potassium permanganate in portions, and stir in an ice water bath; the dosage ratio of the flake graphite powder, concentrated sulfuric acid, phosphoric acid and potassium permanganate is 1g:75-85ml:8-12ml:5-7g.

[0013] Step 1.2: Raise the temperature to 55-65°C and keep warm for 10-15 hours.

[0014] Step 1.3: Transfer the product to ice water, slowly add hydrogen peroxide under stirring until the solution turns golden yellow, filter, wash with dilute hydrochloric acid and deionized water alternately until neutral, and finally add the product to water and disperse it ultrasonically.

[0015] Preferably, in step 1.1, the stirring time is 0.5-1.5h.

[0016] Preferably, in step 1.1: the potassium permanganate is added in 3-6 portions.

[0017] Preferably, in step 1.3: the concentration of the dilute hydrochloric acid is 5-15wt%.

[0018] Preferably, in step 1.3: the ultrasonic time is 9-12h.

[0019] Preferably, in step 2: the cobalt compound is Co(NO3)2·6H2O.

[0020] Preferably, in step 2: the acid is dilute nitric acid, and more preferably the concentration of the dilute nitric acid is 10-30 wt %.

[0021] Preferably, in step 2: the first stirring time is 2-6 hours; the ultrasonic power is 110-130 W, and the ultrasonic time is 6-12 hours; the second stirring time is 2-6 hours; and the drying temperature is 80-120°C.

[0022] Preferably, in step 3: the heating rate is 5-15°C / min.

[0023] Compared with the prior art, the present invention has the following technical effects:

[0024] (1) The present invention uses excess Co 2+ On the one hand, the ions are adsorbed on the surface of the ZIF framework through coordination, and on the other hand, the positively charged ions can be combined with the negatively charged graphene oxide through electrostatic adsorption, thereby ensuring the effective combination of ZIF-67 and graphene oxide with good stability. On this basis, graphene oxide, with the three-dimensional structure of ZIF and excess Co 2+ Ions are used as crosslinking agents to form a three-dimensional graphene precursor, which allows ZIF-67 nanoparticles to be wrapped in graphene oxide sheets in an acidic environment. Finally, p-type doped three-dimensional graphene wrapped ZIF composite absorber is obtained by high-temperature doping.

[0025] (2) The present invention uses graphene oxide to prepare three-dimensional graphene, so that the graphene can effectively prevent itself from stacking in the composite material, maintain its unique structure, and maintain its excellent electrical conductivity.

[0026] (3) The present invention utilizes borane as a protective gas, a reducing agent, and a boron source as a doping agent, thereby shortening the experimental time and steps, being convenient and fast, and being capable of large-scale preparation.

[0027] (4) The present invention utilizes the high temperature doping principle to perform p-type doping on three-dimensional graphene, thereby increasing the carrier concentration and achieving better impedance matching, thereby making its wave absorbing performance more excellent. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the embodiments.

[0029] Example 1

[0030] Step 1: First, add 1g of flake graphite, 80ml of concentrated sulfuric acid, and 10ml of phosphoric acid into a three-necked flask, put the mixture flask into an ice-water bath, and then add potassium permanganate in batches, three times, 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and maintain the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the filtrate pH is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0031] Step 2: Pour 100g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 100mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 3, then place it on a constant temperature stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then place it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0032] Step 3: Place the powder in step 2 above in a quartz boat, and then place it in the center of the tube furnace, slowly introduce borane gas, and then adjust the temperature of the tube furnace to 700°C, and the heating rate is 10°C / min. Put in the furnace plug to control the borane gas flow rate to perform reduction and doping calcination. Finally, keep the constant temperature for 4 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0033] Example 2

[0034] Step 1: First, add 1g of flake graphite, 80ml of concentrated sulfuric acid, and 10ml of phosphoric acid into a three-necked flask, put the mixture flask into an ice-water bath, and then add potassium permanganate in batches, three times, 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and maintain the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the filtrate pH is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0035] Step 2: Pour 100g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 200mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 3, then place it on a thermostatic stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then place it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0036] Step 3: Place the powder in step 2 above in a quartz boat, and then place it in the center of the tube furnace. Slowly introduce borane gas, then adjust the temperature of the tube furnace to 900°C, the heating rate to 10°C / min, and put in a furnace plug to control the flow of borane gas for reduction and doping calcination. Finally, keep the temperature constant for 4 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0037] Example 3

[0038] Step 1: First, add 1g flake graphite, 80ml concentrated sulfuric acid, and 10ml phosphoric acid into a three-necked flask, put the mixture flask into an ice water bath, and then add potassium permanganate in batches, add three times, add 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and keep the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the pH of the filtrate is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0039] Step 2: Pour 100g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 200mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 3, then place it on a thermostatic stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then place it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0040] Step 3: Place the powder in the above step 2 in a quartz boat, and then place it in the center of the tube furnace, slowly introduce borane gas, and then adjust the temperature of the tube furnace to 900°C, the heating rate to 10°C / min, and put in the furnace plug to control the borane gas flow rate for reduction and doping calcination. Finally, keep the constant temperature for 6 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0041] Comparative Example 1

[0042] Step 1: First, add 1g of flake graphite, 80ml of concentrated sulfuric acid, and 10ml of phosphoric acid into a three-necked flask, put the mixture flask into an ice-water bath, and then add potassium permanganate in batches, three times, 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and maintain the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the filtrate pH is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0043] Step 2: Pour 80g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 200mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 3, then put it on a thermostatic stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then put it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0044] Step 3: Place the powder in the above step 2 in a quartz boat, and then place it in the center of the tube furnace, slowly introduce borane gas, and then adjust the temperature of the tube furnace to 900°C, the heating rate to 10°C / min, and put in the furnace plug to control the borane gas flow rate for reduction and doping calcination. Finally, keep the constant temperature for 6 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0045] Comparative Example 2

[0046] Step 1: First, add 1g of flake graphite, 80ml of concentrated sulfuric acid, and 10ml of phosphoric acid into a three-necked flask, put the mixture flask into an ice-water bath, and then add potassium permanganate in batches, three times, 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and maintain the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the filtrate pH is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0047] Step 2: Pour 100g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 200mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 5, then place it on a constant temperature stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then place it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0048] Step 3: Place the powder in the above step 2 in a quartz boat, and then place it in the center of the tube furnace, slowly introduce borane gas, and then adjust the temperature of the tube furnace to 900°C, the heating rate to 10°C / min, and put in the furnace plug to control the borane gas flow rate for reduction and doping calcination. Finally, keep the constant temperature for 6 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0049] Comparative Example 3

[0050] Step 1: First, add 1g of flake graphite, 80ml of concentrated sulfuric acid, and 10ml of phosphoric acid into a three-necked flask, put the mixture flask into an ice-water bath, and then add potassium permanganate in batches, three times, 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and maintain the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the filtrate pH is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0051] Step 2: Pour 100g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 200mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 3, then place it on a thermostatic stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then place it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0052] Step 3: Place the powder in the above step 2 in a quartz boat, and then put it in the center of the tube furnace, slowly introduce borane gas, and then adjust the temperature of the tube furnace to 900°C, the heating rate to 15°C / min, and put in the furnace plug to control the borane gas flow rate for reduction and doping calcination. Finally, keep the constant temperature for 6 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0053] Comparative Example 4

[0054] Step 1: First, add 1g of flake graphite, 80ml of concentrated sulfuric acid, and 10ml of phosphoric acid into a three-necked flask, put the mixture flask into an ice-water bath, and then add potassium permanganate in batches, three times, 2g each time, with an interval of 10s, and stir for 1h. Then raise the temperature of the flask to 60°C and maintain the temperature for 12h. Then pour the product in the bottle into ice water, slowly add hydrogen peroxide while stirring until the solution turns golden yellow, pour it into a funnel with filter paper, filter it, and then wash it alternately with 10% dilute hydrochloric acid and deionized water until the filtrate pH is about 7, and then put the graphene oxide on the filter paper into a beaker filled with deionized water, put it into an ultrasonic machine and ultrasonicate it at 120W for 10h to obtain a graphene oxide dispersion.

[0055] Step 2: Pour 100g of ZIF-67(Co) into the above ultrasonic graphene oxide dispersion, stir for 2h, ultrasonic for 6h, then add 200mg of cobalt nitrate and stir for 2h, ultrasonic for 10h, then add 15% dilute nitric acid to reduce the pH value of the solution to about 3, then place it on a thermostatic stirrer and adjust the temperature to 80°C, stir until the water is basically evaporated, then place it in a drying oven for 15h at 110°C. Dry it into powder and collect it.

[0056] Step 3: Place the powder in the above step 2 in a quartz boat, and then place it in the center of the tube furnace, first slowly introduce borane gas, then adjust the temperature of the tube furnace to 900°C, the heating rate to 5°C / min, and put in a furnace plug to control the borane gas flow rate for reduction, doping and calcination. Finally, keep the constant temperature for 6 hours. When the tube furnace cools to room temperature, close the borane gas valve, take out the sample, and obtain a high-quality p-type doped three-dimensional graphene-wrapped ZIF composite absorber.

[0057] Performance Testing

[0058] The samples of each embodiment and comparative example were fully mixed with molten paraffin to prepare cylindrical samples with an inner diameter of 3.0 mm and an outer diameter of 7.0 mm. The minimum reflection loss and absorption bandwidth were tested, and then the samples and other variables were aggregated into the following table:

[0059]

[0060] By comparing Examples 1-3, it can be clearly concluded that the final reduction sintering temperature and sintering time have a great influence on the absorbing performance of the absorbing material. Obviously, the higher the sintering temperature, the better the reduction of graphene and boron doping, and the longer the sintering time, the better the reduction of graphene and boron doping, and the better the absorbing performance.

[0061] Comparing Example 3 with Comparative Example 1, it is obvious that a smaller amount of ZIF will affect the formation of the three-dimensional graphene structure, thereby reducing the wave absorbing performance of the material.

[0062] Comparing Example 3 with Comparative Example 2, it is obvious that if the pH is too high during pH adjustment, ZIF cannot effectively collapse to form a three-dimensional graphene-wrapped structure, thus affecting the microwave absorbing performance.

[0063] Comparing Example 3 with Comparative Example 3 and Comparative Example 4, it is obvious that the heating rate, sintering temperature and sintering time will affect the performance of the material and need to be strictly controlled.

[0064] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material, characterized in that: The steps include: Step 1: preparing graphene oxide dispersion; Step 1.1: Mix flake graphite powder, concentrated sulfuric acid and phosphoric acid in a container, add potassium permanganate in portions, and place in an ice water bath for stirring; the amount ratio of flake graphite powder, concentrated sulfuric acid, phosphoric acid and potassium permanganate is 1g:75-85ml:8-12ml:5-7g; Step 1.2: Heat to 55-65°C and keep warm for 10-15 hours; Step 1.3: Transfer the product to ice water, slowly add hydrogen peroxide under stirring until the solution turns golden yellow, filter, wash with dilute hydrochloric acid and deionized water alternately until neutral, and finally add the product to water and disperse by ultrasonication; Step 2: Mix ZIF-67 (Co) and graphene oxide dispersion in a ratio of 100-110 g: 200 mL, stir evenly and add excess Co-containing 2+ The cobalt compound is subjected to ultrasonic treatment, and then acid is added to adjust the pH to below 3.5, and heated and stirred at 75-85° C. in air until the water is basically evaporated, and then dried to obtain a three-dimensional graphene-wrapped ZIF powder; Step 3: Put the three-dimensional graphene-wrapped ZIF powder obtained in step 2 into a tubular furnace, introduce borane, heat to 700-1100°C at a heating rate of 5-15°C / min, and sinter for 2-8 h to obtain a p-type doped three-dimensional graphene-wrapped ZIF composite absorbing material.

2. The preparation method according to claim 1, characterized in that: In step 1.1: stirring time is 0.5-1.5h.

3. The preparation method according to claim 1, characterized in that: In step 1.1: the potassium permanganate is added in 3-6 portions.

4. The preparation method according to claim 1, characterized in that: In step 1.3: the concentration of the dilute hydrochloric acid is 5-15wt%.

5. The preparation method according to claim 1, characterized in that: In step 1.3: the ultrasonication time is 9-12 h.

6. The preparation method according to claim 1, characterized in that: In step 2: the cobalt compound is Co(NO3)2·6H2O.

7. The preparation method according to claim 1, characterized in that: In step 2: the acid is dilute nitric acid.

8. The preparation method according to claim 1, characterized in that: In step 2: the first stirring time is 2-6 h; the ultrasonic power is 110-130 W, and the ultrasonic time is 6-12 h; the second stirring time is 2-6 h; and the drying temperature is 80-120 °C.

Citation Information

Patent Citations

  • Preparation and application of three-dimensional bulk-phase graphene-based cobalt-based MOFs (metal-organic frameworks) composite materials

    CN108889336A

  • Preparation method of ZIF-67 reduced graphene oxide microwave absorbing composite material (CoC-rGo)

    CN108997971A